Korelasi antara Hari Berbahasa Inggris dan Penguasaan Grammar dalam Meningkatkan Kemampuan Berbicara Siswa - Hayati, Nur; Ardiya; Siti Niah (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2026)
The purpose of this study was to evaluate the relationship between the English day program and grammar mastery at Ummul Quro' Islamic Boarding School. Quantitative methods were used in this study, and the research tools used were questionnaires and grammar mastery tests. The population of this study was all students at Ummul Quro' Islamic Boarding School, which consisted of four classes with a total of 111 students. The sample was taken using a simple random sampling process. In addition, a number of people were randomly selected to be the sample of this study based on the names taken previously. The results of the analysis showed that there was no significant correlation between the English day program and their grammar mastery. This can be seen from the data significance value of 0.473 which is more than 0.05. The Pearson correlation value is -0.161, which indicates a very low level and a negative linear relationship, which means H1 is rejected and H0 is accepted. It can be concluded that the English day program which is implemented regularly does not affect their grammar mastery.